(untitled) (Research, Society and Development, 2022)
Around the world, millions of cancer cases are diagnosed, among them, 10% are the result of genetic anomalies caused in the oral cavity, giving rise to the so-called mouth cancer. This neoplasm has several risk factors, this work aims to emphasize and analyze the relationship of smoking by electronic cigarettes (Ces) with the development of oral cancer. The (Ces) has become popular and gradually become more accessible over the years. As it is a mixture of toxic and dangerous substances, in addition to generating heated gases, it has relevant consequences for the user’s oral health. For the construction of this work, a bibliographic survey was carried out, with the help of the Health Sciences Descriptors (DECS): Mouth cancer, electronic cigarette, vapping and oral cancer. The following databases were used: Research, Society and Development, Scientific Electronic Library Online (Scielo) and National Library of Medicine PUBMED, with the help of the Mendeley reference management program in the organization of the selected articles. from the studies and conclusions of the authors, it was identified that the substances and hot vapors formed when using these devices are factors that influence cell modification, therefore, the consumption of electronic cigarettes can influence the formation of oral cancer. educational and consumption reduction, educating users about the harm of this product, in addition to oral cancer prevention campaigns, are actions that can and should be taken to improve public health.